THE KEMALIST DISCOURSE AND A PARADIGM SHIFT IN TURKISH POLITICS (Journal of Oriental Studies, 2026)
This study examines the conceptual, intellectual, ideological, and historical roots of the kemalist discourse, as well as the theoretical foundations of Westernization, modernization, and secularization of Turkish society. The aim of the research is to analyze the role of kemalist discourse in Turkish politics and to identify the paradigm shift from kemalism to alternative political discourses. The objectives include identifying the strengths of kemalism and revealing its weaknesses and limitations amid profound political transformations and changes in Turkey’s domestic and foreign policy.The relevance of the study is determined by the decline of the dominant kemalist discourse and the rise of alternative political ideologies, particularly following the coming to power of the Justice and Development Party. The methodology is based on a critical review of academic literature and historical sources, as well as methods of historical analysis and critical discourse analysis. These approaches make it possible to examine how the kemalist discourse shaped the secular republican political order andguided the development of Turkish society since the foundation of the republic.The findings show that kemalism functioned as a hegemonic ideology of state and nation-building, transforming Turkey from an Eastern political entity into a modern, Westernized, and secular state. During the nation-building process, the kemalist elite focused on constructing a new secular and Westernoriented national identity, marginalizing Islam, the Ottoman past, and certain ethno-religious minorities. At the same time, internal contradictions of kemalism were revealed, which contributed to the rise of conservative and Islamist movements and the search for a new national paradigm. The study enhances understanding of the complexity and trends of contemporary Turkish politics and provides a foundation for further research.Keywords: kemalism, Turkey, nationalism, secularism, Westernization, Islam, neo-Ottomanism.